Colonic diverticular bleeding and predictors of the length of hospitalization: An observational study. Issue 8 (29th January 2019) - Wada, Michiko; Nishizawa, Toshihiro; Kato, Motohiko; Hirai, Yuichiro; Kinoshita, Satoshi; Mori, Hideki; Nakazato, Yoshihiro; Fujimoto, Ai; Kikuchi, Masahiro; Uraoka, Toshio; Kanai, Takanori
Abstract: Background and Aim: A significant percentage of patients with colonic diverticular bleeding (CDB) experience bleeding that is severe enough to necessitate prolonged hospitalization. Prolonged hospitalization causes deterioration in patients' quality of life, as well as difficulties with cost‐effective utilization of medical resources, and is a financial burden to the society. Therefore, we investigated the factors associated with the length of hospitalization for the optimal management of patients hospitalized with CDB. Methods: This study included patients who were hospitalized for the treatment of CDB and underwent colonoscopy between July 2008 and February 2016. Logistic regression analysis was performed to investigate the association between the length of hospitalization and the patients' baseline characteristics, in‐hospital procedures performed, and the clinical outcomes. Results: The study included 223 patients. Diabetes mellitus (odds ratio [OR] 3.4, P  = 0.014) and blood transfusion (OR 3.1, P  = 0.0006) were identified as risk factors for prolonged hospitalization (≥ 8 days). Urgent colonoscopy (OR 0.41, P  = 0.0072) predicted a shorter length of hospitalization (≤ 7 days). The study also indicated that endoscopic treatment showed a stronger association with urgent colonoscopy (OR 7.8, P  < 0.0001) than with elective colonoscopy and that urgent colonoscopy was not associated with an increased rate of adverse events or re‐bleeding. Conclusions: Compared with elective colonoscopy, urgent colonoscopy shortens the length of hospitalization in patients with CDB. Moreover, it is not associated with an increased rate of adverse events. Urgent colonoscopy may be impracticable in a few cases; however, if possible, aggressive urgent colonoscopy should be considered for the efficient management of the patient's hospital stay.